The media view of the 1979 european election campaign - Kelly, Mj (Economic & Social Studies, 1983)
Abstract: This paper argues that the television presentation of the first direct election to the European Parliament in Ireland was more domestic in orientation than either the parties' own presentations on television or voter attitudes might have led one to expect. It seeks to understand how this pattern of coverage emerged by examining the timing of the European election in Ireland; the pre-campaign newspaper speculation regarding the European elections and the extent of the press's subsequent agenda-setting functions; the programme formats within which the European election campaign was presented on RTE; and finally the attitudes of broadcasters to this election and to the audience for European election programmes.
Keywords: Economics; Sociology